2020
DOI: 10.3390/ijms21082740
|View full text |Cite
|
Sign up to set email alerts
|

RNAseq-Based Prioritization Revealed COL6A5, COL8A1, COL10A1 and MIR146A as Common and Differential Susceptibility Biomarkers for Psoriasis and Psoriatic Arthritis: Confirmation from Genotyping Analysis of 1417 Italian Subjects

Abstract: Psoriasis (Ps) and Psoriatic Arthritis (PsA) are characterized by a multifactorial etiology, involving genetic and environmental factors. The present study aimed to investigate polymorphisms (SNPs) within genes involved in extracellular matrix and cell homeostasis and microRNA genes as susceptibility biomarkers for Ps and PsA. Bioinformatic analysis on public RNA-seq data allowed for selection of rs12488457 (A/C, COL6A5), rs13081855 (G/T, COL8A1), rs3812111 (A/T, COL10A1) and rs2910164 (C/G, MIR146A) as candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 40 publications
(62 reference statements)
1
17
0
Order By: Relevance
“…However, the expression of COL6A5 in the papillary dermis 42 suggested a potential association with Ps and PsA, given the fact that the papillary dermis can be affected in both disorders. Supporting this hypothesis, we found a significant association of rs12488457 (A/C) variant located in COL6A5 with Ps and PsA in a recent study on the Italian population 48 …”
Section: Maintenance Of Skin Structure and Integrity: The Role Of Colsupporting
confidence: 72%
See 4 more Smart Citations
“…However, the expression of COL6A5 in the papillary dermis 42 suggested a potential association with Ps and PsA, given the fact that the papillary dermis can be affected in both disorders. Supporting this hypothesis, we found a significant association of rs12488457 (A/C) variant located in COL6A5 with Ps and PsA in a recent study on the Italian population 48 …”
Section: Maintenance Of Skin Structure and Integrity: The Role Of Colsupporting
confidence: 72%
“…In this context, mutations in these genes have been associated with different forms of chondrodysplasia 36 and increased levels of collagen X have been found in the serum of PsA patients 52 . On this subject, we found that the COL10A1 ‐rs3812111 (T/A) variant was exclusively associated with PsA, suggesting the possible contribution of bone metabolism‐related factors in the differential etiopathogenesis of PsA compared to Ps 48 . Given these data and considering the role of collagen genes in the maintenance of bone homeostasis, their investigation may provide interesting insights into different etiopathogenetic pathways underlying Ps and PsA 53 …”
Section: Maintenance Of Skin Structure and Integrity: The Role Of Colmentioning
confidence: 63%
See 3 more Smart Citations